2002
DOI: 10.1038/sj.bjp.0704896
|View full text |Cite
|
Sign up to set email alerts
|

Fructose‐1,6‐diphosphate attenuates prostaglandin E2 production and cyclo‐oxygenase‐2 expression in UVB‐irradiated HaCaT keratinocytes

Abstract: 1 Fructose-1,6-diphosphate (FDP), a glycolytic metabolite, is reported to ameliorate in¯ammation and inhibit the nitric oxide production in murine macrophages stimulated with endotoxin. It is also reported that FDP has cytoprotective eects against hypoxia or ischaemia/reperfusion injury in brain and heart. However, underlying mechanisms of its various biological activities are not completely understood. 2 In this study, we examined the eects of FDP on UVB-induced prostaglandin production in HaCaT keratinocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 45 publications
2
24
0
2
Order By: Relevance
“…Additionally, it has been reported that FBP also has the immunomodulatory function [6], although the mechanism for this has not yet been clearly identified. FBP attenuated prostaglandin E 2 production and cyclooxygenase-2 (COX-2) expression in UVB-irradiated HaCaT keratinocytes [1], and inhibited LPS-induced iNOS expression in macrophages with no reduction of NF-kB activity [12]. ROS and reactive nitric oxide species that have neurotoxic properties are formed by the activity of inducible nitric oxide synthase (iNOS), which is also activated via MAPK [14].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that FBP also has the immunomodulatory function [6], although the mechanism for this has not yet been clearly identified. FBP attenuated prostaglandin E 2 production and cyclooxygenase-2 (COX-2) expression in UVB-irradiated HaCaT keratinocytes [1], and inhibited LPS-induced iNOS expression in macrophages with no reduction of NF-kB activity [12]. ROS and reactive nitric oxide species that have neurotoxic properties are formed by the activity of inducible nitric oxide synthase (iNOS), which is also activated via MAPK [14].…”
Section: Discussionmentioning
confidence: 99%
“…UVB-induced erythema is attenuated by the NOS inhibitor NG-monomethyl-L-arginine and the cyclooxygenase (COX) inhibitor indomethacin [26]. ROS, including NO, induce skin erythema through prostaglandin E2 synthesis [27]. Expression of COX-2, a pivotal enzyme in prostaglandin E2 synthesis, is upregulated by ROS to stimulate the inflammation process [28].…”
Section: Inflammationmentioning
confidence: 99%
“…Fructose-1,6-bisphosphate is capable of inhibiting pleurisy induced by carrageenan [26]. The sugar is also capable of exercising a protective effect by attenuating the production of prostaglandin E and the expression of COX-2 [27], as well as controlling the secretion of cytokines and the production of nitric oxide [28]. We have shown that this sugar is effective as an anti-inflammatory agent in pleurisy induced by EBD, reducing cellular infiltration and plasma exudation, suggesting that the EBD may provoke an increase in prostaglandin E and of COX-2 activity.…”
Section: Discussionmentioning
confidence: 99%